Current View of the Problem: A New Approach to Covid-19 Treatment - Jasur A. Rizaev1, Ezozbek A. Rizaev2, N.N. Akhmadaliev3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Coronavirus infection COVID-19 (acronym for Corona Virus Disease 2019), formerly Coronavirus infection2019-nCoV is a potentially severe acute respiratory infection caused by SARS-CoV-2. It is a dangerousdisease that can take the form of an acute respiratory viral infection of the lung or a severe form, the specificcomplications of which may include viral pneumonia leading to acute respiratory distress syndrome orrespiratory failure with a risk of death.